Importin-8 Modulates Division of Apical Progenitors, Dendritogenesis and Tangential Migration During Development of Mouse Cortex - Nganou, Gerry; Silva, Carla G.; Gladwyn-Ng, Ivan; Engel, Dominique; Coumans, Bernard; Delgado-Escueta, Antonio V.; Tanaka, Miyabi; Nguyen, Laurent; Grisar, Thierry; de Nijs, Laurence; Lakaye, Bernard (Frontiers in Molecular Neuroscience, 2018)
The building of the brain is a multistep process that requires the coordinate expression of thousands of genes and an intense nucleocytoplamic transport of RNA and proteins. This transport is mediated by karyopherins that comprise importins and exportins. Here we investigated the role of the ß-importin IPO8 during mouse cerebral corticogenesis as several of its cargoes have been shown to be essential during this process. First, we showed that Ipo8 mRNA is expressed in mouse brain at various embryonic ages with a clear signal in the sub-ventricular/ventricular zone, the cerebral cortical plate and the ganglionic eminences. We found that acute knockdown of IPO8 in cortical progenitors reduced both their proliferation and cell cycle exit leading to the increase in apical progenitor pool without influencing the number of basal progenitors. Projection neurons ultimately reached their appropriate cerebral cortical layer, but their dendritogenesis was specifically affected, resulting in neurons with reduced dendrite complexity. IPO8 knockdown also slowed the migration of cortical interneurons. Together, our data demonstrate that IPO8 contribute to the coordination of several critical steps of cerebral cortex development. These results suggest that the impairment of IPO8 function might be associated with some diseases of neuronal migration defects.